OCCUPATIONAL SAFETY IN CIVIL CONSTRUCTION OF THE STATE OF RORAIMA - do Carmo Merlim Neto, Orlando (Journal of Interdisciplinary Debates, 2024)
This research highlights the safety of work in civil construction in the state of Roraima, with the objective of analyzing the safety practices adopted in the sector, identifying the main risks faced and assessing the effectiveness of implemented preventive measures. The methodology was based on the analysis of regulatory standards, local case studies and workers’ perception. The results showed that Roraima’s climate and geographical particularities impose additional security challenges, highlighting the importance of adapted practices and effective risk management. The conclusion points to the need to strengthen security culture in companies, with emphasis on workers’ education and training, as a way to reduce accidents and improve working conditions.